A Novel XRE-Type Regulator Mediates Phage Lytic Development and Multiple Host Metabolic Processes in Pseudomonas aeruginosa - Xiang Long; Xiaolong Wang; Daqing Mao; Weihui Wu; Yi Luo (Microbiology Spectrum, 2022)
ABSTRACT Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen, the leading cause of acute and chronic infections in immunocompromised patients, frequently with high morbidity and mortality rates. The xenobiotic response element (XRE) family proteins are the second most common transcriptional regulators (TRs) in P. aeruginosa. However, only a few XRE-like TRs have been reported to regulate multiple bacterial cellular processes, encompassing virulence, metabolism, antibiotic synthesis or resistance, stress responses, and phage infection, etc. Our understanding of what roles these XRE-like small regulatory proteins play in P. aeruginosa remains limited. Here, we aimed to decipher the role of a putative XRE-type transcriptional regulator (designated LfsT) from a prophage region on the chromosome of a clinical P. aeruginosa isolate, P8W. Southern blot and reverse transcription quantitative PCR (RT-qPCR) assays demonstrated that LfsT controlled host sensitivity to the phage PP9W2 and was essential for efficient phage replication. In addition, electrophoretic mobility shift assays (EMSAs) and transcriptional lacZ fusion analyses indicated that LfsT repressed the lysogenic development and promoted the lytic cycle of phage PP9W2 by binding to the promoter regions of the gp71 gene (encoding a CI-like repressor) and several vital phage genes. Combined with RNA-seq and a series of phenotypic validation tests, our results showed that LfsT bound to the flexible palindromic sites within the promoters upstream of several genes in the bacterial genome, regulating fatty acid (FA) metabolism, spermidine (SPD) transport, as well as the type III secretion system (T3SS). Overall, this study reveals novel regulatory roles of LfsT in P. aeruginosa, improving our understanding of the molecular mechanisms behind bacterium-phage interactions. IMPORTANCE This work elucidates the novel roles of a putative XRE family TR, LfsT, in the intricate regulatory systems of P. aeruginosa. We found that LfsT bound directly to the core promoter regions upstream of the start codons of numerous genes involved in various processes, including phage infection, FA metabolism, SPD transport, and the T3SS, regulating as the repressor or activator. The identified partial palindromic motif NAACN(5,8)GTTN recognized by LfsT suggests extensive effects of LfsT on gene expression by maintaining preferential binding to nucleotide sites under evolutionary pressure. In summary, these findings indicate that LfsT enhances metabolic activity in P. aeruginosa, while it reduces host resistance to the phage. This study helps us better understand the coevolution of bacteria and phages (e.g., survival comes at a cost) and provides clues for designing novel antimicrobials against P. aeruginosa infections.